2017
DOI: 10.3390/su9101766
|View full text |Cite
|
Sign up to set email alerts
|

How Urbanization Economies Impact TFP of R&D Performers: Evidence from China

Abstract: There have been extensive studies exploring the relationship between agglomeration economies and economic growth. However, far less attention is paid to the nonlinear relationship of urbanization economies-firm productivity nexus, especially in developing countries. This paper aims to explore how urbanization economies impact the total factor productivity (TFP) of research and development (R&D) performers using a large sample of Chinese manufacturing firms. The generalized propensity score matching methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…As a result, the findings on externality theories inside and outside enterprises gradually formed an important theoretical basis for agglomeration economies [19][20][21]. At the same time, agglomeration economies were gradually confirmed in extensive empirical research and accepted as a major driving force in regional economic development [22][23][24].…”
Section: Literature Reviewmentioning
confidence: 93%
“…As a result, the findings on externality theories inside and outside enterprises gradually formed an important theoretical basis for agglomeration economies [19][20][21]. At the same time, agglomeration economies were gradually confirmed in extensive empirical research and accepted as a major driving force in regional economic development [22][23][24].…”
Section: Literature Reviewmentioning
confidence: 93%
“…However, this study used a provincial fixed effect model and did not adopt the DID method, thus casting doubt on the robustness of the results obtained. Dai et al [26] used enterprise-level data and found that while the development of the western region improved enterprise total factor productivity (TFP); this effect had weakened over time. Liu et al [27] applied the triple-difference method and found that the WDS has increased the number of enterprises in the counties on the west side of the western provincial boundary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the case of Italy, see Chiarini and Marzano (2018). In China, Dai et al (2017) reveal nonlinear relationship between urbanization and TFP. According to their findings, there is an optimal point for the relationship between urbanization rate and TFP to be maximized.…”
Section: Empirical Evidencementioning
confidence: 99%